Exploring gender bias, belonging, and prejudice among IT students in higher education - G. Luciano, Ruth (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study investigates gender discrimination, inclusion, and belonging among information technology (IT) students in higher education, with specific objectives to assess their sense of belonging, classroom participation, and perceptions of gender bias. The research aims to identify persistent issues related to gender equity and propose actionable solutions to foster inclusivity. Using a descriptive research design, the study surveyed 180 student-leaders, purposively selected to represent various year levels and provide diverse insights into academic and extracurricular experiences. Data were collected through a structured questionnaire adapted and modified to fit the study’s context. The instrument included Likert-scale items focusing on dimensions such as belonging, teaching environment, gender discrimination, and prejudice. Findings reveal that while most students feel respected by peers and professors, subtle forms of gender bias continue to affect female students, limiting role models and occasionally undermining their confidence and engagement. Practical implications highlight the need for gender-sensitive curricula, mentorship programs, and policy adjustments to create a more inclusive academic environment. Recommendations include increasing female representation in leadership roles, conducting gender sensitivity training, and diversifying course materials. These strategies aim to enhance gender equity, support student success, and establish a culture of inclusion within IT education.